High seroprevalence of pathogenic Yersinia spp. in sheep and goats across nine government farms in the Pakistani Punjab - Qudrat Ullah; Tariq Jamil; Muhammad H Hussain; Huma Jamil; Muhammad Saqib; Usman Tahir; Heinrich Neubauer; Lisa D Sprague (Journal of Infection in Developing Countries)
Introduction: Seroprevalence of Y. enterocolitica and Y. pseudotuberculosis infections in animals and humans is not established in Pakistan. There are only a few reports on the prevalence of pathogenic Yersinia spp. and infections in small ruminants, however, the role of sheep and goats in the transmission of pathogenic Yersinia remains unclear.